Where and why? Bees, snail shells and climate: Distribution of Rhodanthidium (Hymenoptera: Megachilidae) in the Iberian Peninsula. Issue 3 (27th May 2020) - Romero, Daniel; Ornosa, Concepción; Vargas, Pablo
Abstract: Species distribution patterns are widely studied through species distribution models (SDMs), focusing mostly on climatic variables. Joint species distribution models (JSDMs) allow inferring if other factors (biotic interactions, shared phylogenetic history or other unmeasured variables) can also have an influence on species distribution. We identified current distributional areas and optimal suitability areas of three species of the solitary snail‐shell bee Rhodanthidium (Hymenoptera: Megachilidae), and their host gastropod species in the Iberian Peninsula. We undertook SDMs using Maxent software, based on presence points and climatic variables. We also undertook JSDMs for the bees and the snails to infer if co‐occurrence could be a result of biotic interactions. We found that the three bee species: (1) use at least five different species of Mediterranean snails; (2) use empty shells not only for nesting but also for sheltering when there is adverse weather and during the night; (3) have their most suitable areas in the eastern and southern Iberian Peninsula, mostly on limestone areas; and (4) have their optimal range under Mediterranean climatic values for the studied variables. There is positive co‐occurrence of Rhodanthidium with the gastropod species, especially with the snail Sphincterochila candidissima . The contribution of the environmental component to the co‐occurrence is less than that of the residual component in those cases, suggesting that: (i) the use of biotic resources (between Rhodanthidium and the gastropod species); (ii) shared phylogenetic history (between R. septemdentatum and R. sticticum ); or (iii) unmeasured variables are largely responsible for co‐occurrence. Abstract :